THE EFFECT OF AEROBIC TRAINING ON SOME CHEMICAL INDICATORS AMONG HANDBALL YOUTH - M. Abbas Mohsen Aliwi (Proximus Journal Publishing, 2024)
The research problem focused on the training methods used in developing aerobic training for young handball players due to the lack of use of modern technologies, especially with regard to measuring the physiological and chemical variables of the muscles. The objectives of the research included -:Identify some chemical indicators in young handball players - .Preparing training curricula to develop study variables for young handball players. The research methodology and field procedures included: The researcher’s adoption of the experimental method for its suitability and the nature of the research. The research population and sample reached (20) youth handball players for the season (2023-2024) for the forums Youth in Dhi Qar Governorate. The most important conclusions are: - Effects of the aerobic training method appeared on each of the variables investigated (HB, WBCS, chlorine, sodium, potassium, calcium -The exercises have significant effects, as the circular training method and the low-intensity interval training method have a positive effect on the variables investigated
Keywords: variables; method; training; intensity